Does Teacher Immediacy Affect Students? A Systematic Review of the Association Between Teacher Verbal and Non-verbal Immediacy and Student Motivation - Liu, Wei (Frontiers in Psychology, 2021)
In instructional-learning contexts, the relationship between teacher verbal and non-verbal immediacy and student motivation has gained increasing attention. However, no systematic research has been done to review the empirical studies conducted on the impact of teacher immediacy on students' motivation. Hence, the aim of the present study was to systematically review the available literature on different types of teacher immediacy and student motivation. Some common databases were searched and 30 eligible manuscripts were identified. With regard to the key features of the included studies, the review's findings were categorized into different sections, namely “the measures of teacher immediacy employed,” “the measures of student motivation employed,” “designs,” and “educational contexts”. The main findings of the studies were also discussed. The reviewed studies pointed to positive associations between teacher immediacy and student motivation. Finally, limitations of the included studies are discussed and some practical directions for further research are offered, accordingly.